Decisions with moral content: Collusion - Zarkada, Anna K.; Skitmore, Martin (My University, 2000)
Morality is fast becoming an integral part of the mandate for business through both societal and regulatory pressures. Collusive tendering is one of the moral choices facing decision-makers in the construction industry. This paper describes an empirical investigation of the attitudes and behavioural intent towards collusive tendering of key individuals in the tendering process. It also explores the factors that determine these attitudes. The results of the empirical investigation indicate that there is a minority of decision-makers that admit they would consider participating in some form of collusive tendering agreement under certain circumstances. These people form a distinct group in their demographic as well as decision-making profile.
Keywords: Tendering; Moral decision making; Ethics; Collusion; Australia